Prediction of Early BK Virus Infection in Kidney Transplant Recipients by the Number of Cells With Intranuclear Inclusion Bodies (Decoy Cells). Issue 2 (February 2018) - Yamada, Yoshiteru; Tsuchiya, Tomohiro; Inagaki, Isao; Seishima, Mitsuru; Deguchi, Takashi
Abstract : Background: BK virus (BKV) is the cause of nephropathy. Because BKV nephropathy can progress to graft loss, early diagnosis of BKV infection is very important. In this study, we aimed to investigate the utility of quantifying cells with intranuclear inclusion bodies (decoy cells) in urinary sediment for the screening and monitoring of BKV infection in renal transplant recipients at our hospital. Methods: This was a retrospective single-center study. Urine sediment examination was performed at each outpatient visit, and the number of decoy cells was measured in the whole microscopic field. Patients (n = 41) were divided into the BK viremia group (blood positive for BKV DNA by polymerase chain reaction [PCR]) and non-BK viremia group (blood negative for BKV DNA by PCR), and the decoy cell count in urinary sediments was examined. Results: The maximum decoy cell count was significantly higher ( P = 0.04) in the BK viremia group than in the non-BK viremia group. In the receiver operating characteristic curve for the maximum decoy cells, the cutoff value was 507 cells. The area under the receiver operating characteristic curve was 0.8774 (95% confidence interval, 0.7739-0.9810). The number of decoy cells at the time of appearance in the BK viremia group was not significantly different from that in the non-BK viremia group. However, the BK viremia group showed an increasing trend, whereas the non-BK viremia group showed a decreasing trend, in the number of decoy cells. There was a positive correlation between the number of decoy cells and the data from the urine BKV-DNA PCR quantification (correlation coefficient [ r ] = 0.74). Conclusions: Measurement of decoy cells in urinary sediments may predict early BKV infection, and if performed quickly, it may be useful for screening and continuous monitoring of BKV infection in renal transplant recipients.